2011
DOI: 10.1177/1464884911415974
|View full text |Cite
|
Sign up to set email alerts
|

Reader opinion in the digital age: Tabloid and broadsheet newspaper websites and the exercise of political voice

Abstract: This article explores interactive opportunities provided by British broadsheet and tabloid newspapers' websites and the ways their readers make use of these opportunities to express their opinions. The article presents the results of both a quantitative and a qualitative analysis of national British broadsheet and tabloid newspaper websites. The research reveals some similarities between newspapers -for example, that interactive opportunities remain under utilized -but also some significant differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 13 publications
(9 reference statements)
1
52
2
2
Order By: Relevance
“…As such, our findings in relation to popular newspapers seemed to differ from that of Richardson and Stanyer (2011) who contended that online readers of tabloid papers were drawn to comment on substantive issues rather than on lifestyle and human-interest musings and celebrity and sport stories. We believe that the divergences between our results were mainly caused by the differences in terms of our samples and data sets as well as by the dissimilarities in terms of political and journalistic culture and online readership.…”
Section: Editorial Policies Of Online Newspapers and Reader Commentscontrasting
confidence: 89%
“…As such, our findings in relation to popular newspapers seemed to differ from that of Richardson and Stanyer (2011) who contended that online readers of tabloid papers were drawn to comment on substantive issues rather than on lifestyle and human-interest musings and celebrity and sport stories. We believe that the divergences between our results were mainly caused by the differences in terms of our samples and data sets as well as by the dissimilarities in terms of political and journalistic culture and online readership.…”
Section: Editorial Policies Of Online Newspapers and Reader Commentscontrasting
confidence: 89%
“…Rose and Novas (2004) (Richardson andStanyer, 2011, McQuail 2013), however this is seen by some as increasing the potential for democratic debate in the media (Richardson and Stanyer, 2011). Normative theories of media and society discuss the function of the press in general and journalists in particular.…”
Section: Discussion: Responsibilising Eaters Through the Mediamentioning
confidence: 99%
“…However, the content of online comments cannot be said to be representative of the general public, given that the profile of those commenting is unknown (Laslo, Baram-Tsabari, and Lewenstein 2012) and that the opinions expressed belong to individuals who have access to the internet, and choose to read and comment on online news articles. Previous research has suggested that those who tend to comment on media articles are 'blindly opinionated', that is they use the comments section to voice their own point without engaging in a dialogue with other participants (Richardson and Stanyer 2011). A number of studies have found that the majority of individuals who engage in Strategies for dismissing dietary risks 7 commenting on an article are more likely to make negative comments on or disagree with the subject matter of the article (Freeman 2011;Glenn, Champion, and Spence 2012;Bezreh et al 2012;Chmiel et al 2010;Secko et al 2011).…”
Section: Online Methodology: the News Media's Comments Sectionmentioning
confidence: 99%